Amphoteric center of luminescence in CdS - Artem'jeva, O. O.; Vakulenko, O. V.; Dacenko, O. I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The impurity photoluminescence of cadmium sulphide crystals is studied. The luminescence intensity dependences on temperature from 80 to 300 K are obtained for the bands at 1.7 and 2 eV. The thermal curve of 1.7 eV luminescence intensity has a peak between 100 and 150 K. Both these bands are associated with emission of the center based on the VCd-type intrinsic point defect. The results can be explained within the framework of the theory of amphoteric centers of charge carrier recombination.